2022
DOI: 10.3390/ijerph191912635
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Analyzing Suicidal Ideation on Social Media Using Deep Learning and Machine Learning Models

Abstract: Individuals who suffer from suicidal ideation frequently express their views and ideas on social media. Thus, several studies found that people who are contemplating suicide can be identified by analyzing social media posts. However, finding and comprehending patterns of suicidal ideation represent a challenging task. Therefore, it is essential to develop a machine learning system for automated early detection of suicidal ideation or any abrupt changes in a user’s behavior by analyzing his or her posts on soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…This information can assist in detecting potential high-risk situations or individuals who may require timely attention or specialized care. For example, as the help-seeker’s suicide risk is closely correlated with their expressed sentiments [ 27 ], using ChatGPT to automatically analyze sentiments could potentially detect suicidal ideation at early stages and facilitate the counselor’s intervention accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…This information can assist in detecting potential high-risk situations or individuals who may require timely attention or specialized care. For example, as the help-seeker’s suicide risk is closely correlated with their expressed sentiments [ 27 ], using ChatGPT to automatically analyze sentiments could potentially detect suicidal ideation at early stages and facilitate the counselor’s intervention accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…• Pre-processed CSSR dataset converted to vector using TF-IDF and Word2Vec vectorizers [12,41,48]. • Feature vector is feed into various machine learning classifier which is trained to determine suicide intensity label in depression post.…”
Section: Methodsmentioning
confidence: 99%
“…In NLP features are converted to corresponding vectors referred as embedding. Typical word embedding approaches TF-IDF, Word2Vec, CNN-BiLSTM [12,17,30,48]. It is observed that Text based expression depicts mental illness more clearly compared to other features and is dominant among researchers to detect mental issues effectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the performances of the RF and XGBoost algorithms for classifying the participant assessments on the 5-Item FRAIL, CHS, and SOF indices into robust, pre-frail, and frail, we employed the common evaluation indicators for ML classification: Accuracy ( Equation 7 ), Precision ( Equation 8 ), Recall ( Equation 9 ), and F1 score ( Equation 10 ): ( 35 ).…”
Section: Methodsmentioning
confidence: 99%